Modest Reductions in Kidney Function and Adverse Outcomes in Younger Adults - Hussain, Junayd (Université d'Ottawa / University of Ottawa, 2023)
Chronic kidney disease (CKD) is a complex and progressive condition with limited curative therapies and is associated with both physical comorbidity, impaired health-related quality of life, and financial strain on the healthcare system. Currently, CKD is defined by a fixed threshold of an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2, which coincides with approximately 60% of healthy kidney function, for ≥3 months regardless of age. However, this definition does not account for natural declines in kidney function with advanced age, leaving older individuals (ages >65 years) with naturally lower eGFR and without significant kidney damage being over-diagnosed with CKD. Conversely, there is also concern of underdiagnosis of CKD in younger adults (ages <40 years) with “modest” eGFR reductions (eGFR levels well above 60, but below age-expected values). Indeed, severe impairment is not detected in younger adults until they lose close to 50% of their healthy kidney function, precluding timely prevention of CKD progression and its associated complications (premature mortality, cardiovascular events, etc.). However, whether these “modest” eGFR reductions are associated with elevated clinical risk in younger adults is unknown. This thesis is based on a retrospective cohort study using linked healthcare administrative databases to examine the association of index eGFR categories with time to adverse outcomes, relative to age-specific referents. In the first manuscript, we compared associations with key adverse outcomes (all-cause mortality, cardiovascular events, and kidney failure) and patterns of healthcare utilization between younger (ages 18-39), middle-aged (40-49), and older adults (50-65 years). In the second manuscript, we examined associations with major cardiovascular events (cardiovascular mortality, acute coronary syndrome, ischemic stroke, heart failure) by age group. In both manuscripts, we noted significant elevations in risk of adverse outcomes at higher eGFR levels relative to age-specific referents in younger, compared to middle-aged and older adults. Despite this age-related vii disparity in clinical risk with modestly reduced eGFR, younger adults were least likely to obtain a repeated eGFR measure or be referred to a specialist during follow-up. Notably, these findings persisted for individual adverse events and in clinically important subgroups, as well as after various sensitivity analyses (adjusting for additional comorbidities, defining index eGFR using repeated measures, using common referents, and excluding individuals with different underlying mechanisms for reduced eGFR (pregnancy, acute kidney injury, etc.)). The current thesis presents evidence of elevated clinical risk with modest reductions in kidney function in younger adults, emphasizing the importance of risk-based eGFR thresholds that vary with age and considering modestly reduced eGFR as important cardiovascular risk factors worth monitoring in routine clinical practice.
Keywords: Kidney failure; Clinical epidemiology; Big data; Prevention; Chronic kidney disease; Mortality